Isolation and expression analysis of a gene encoding ACC oxidase in Curcuma alismatifolia Gagnep - S. Mahadtanapuk (2018)
A cDNA fragment encoding ACC oxidase from Curcuma alismatifolia Gagnep. was isolated and its expression analyzed. Primers were designed from highly conserved domains of ACC oxidase from various plant species from GenBank database. The forward and reverse primers were derived from ENWGFFE and TNGKYKS amino acid segment, respectively. The PCR products had length of 600 basepair and were subcloned into pGEM T-easy vector resulting in pCa-ACOI. The deduced amino acid sequence of the cDNA was highly homologous to those of ACC oxidase gene isolated from other plants in NCBI database. Northern blot analysis shows that pCa-ACOI is expressed at petal and bract of curcuma and highly accumulated at day 1 and 3 in petal and bract during postharvest of cut curcuma, respectively. The Ca-ACOI was subcloned pBI121 resulting in pBI121-Ca-ACOI, then transformed into leaf tissues of tobacco (Nicotiana tabacum) via Agrobacterium tumefaciens strain AGLO. Transformation event was confirmed by PCR analysis and a histochemical GUS assay. The transgenic tobacco plants are currently growing in the greenhouse and phenotypic observations are made.